2022
DOI: 10.1177/09622802221106300
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of COVID-19 in-hospital mortality: A competing risk approach or a cure model?

Abstract: Competing risk analyses have been widely used for the analysis of in-hospital mortality in which hospital discharge is considered as a competing event. The competing risk model assumes that more than one cause of failure is possible, but there is only one outcome of interest and all others serve as competing events. However, hospital discharge and in-hospital death are two outcomes resulting from the same disease process and patients whose disease conditions were stabilized so that inpatient care was no longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Their second method entailed an inverse probability weighted Kaplan–Meier estimator that accounted for the eliminated (censored) competing event of discharge alive [ 48 ]. We believe that acknowledging the treatment effects on discharge alive is more meaningful: the interest may be to examine not only how treatment prevents death, but also how treatment affects the probability of recovering from the infection [ 41 ]. We showed that a competing risks analysis provides important insights on treatment effects on all clinically meaningful and heterogeneous end points [ 11 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their second method entailed an inverse probability weighted Kaplan–Meier estimator that accounted for the eliminated (censored) competing event of discharge alive [ 48 ]. We believe that acknowledging the treatment effects on discharge alive is more meaningful: the interest may be to examine not only how treatment prevents death, but also how treatment affects the probability of recovering from the infection [ 41 ]. We showed that a competing risks analysis provides important insights on treatment effects on all clinically meaningful and heterogeneous end points [ 11 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…By definition, a competing risk (e.g., hospital discharge) is an event that prevents the occurrence of the primary outcome (e.g., in-hospital death) of interest [ 39 ]. Our emulated framework fits a simplified three-state competing risks model to estimate transition hazard rates ( Figure 2 ), where in-hospital death and discharge alive are two absorbing events of the same disease [ 40 , 41 ]. Each arrow represents a time-homogeneous hazard rate from the initial state of hospital admission as untreated or treated to the two terminating end points of in-hospital death or discharged alive , respectively.…”
Section: Methodsmentioning
confidence: 99%